The Impact of Legal-Financial Obligations on Relationships With Family, Friends, and Acquaintances: A Qualitative Study of Community Supervised Men With Sexual and Nonsexual Offense Convictions - Giuffre, Andrea (Criminal justice and behavior, 2023)
System-impacted individuals often rely on others to provide financial support, which aids in the payment of legal-financial obligations (LFOs). LFOs comprise the fines, fees, restitution, surcharges, and assessments imposed on individuals who come into contact with the criminal legal system. Limited evidence suggests that this support can prompt stress and negative emotions for system-impacted individuals and their families. This study examines the process by which a matched sample of 125 men convicted of sexual offenses and nonsexual offenses in Missouri obtain financial support from others and how that process impacts their relationships. Secondary qualitative analysis of interviews with these men reveals that financial support may be governed by resource-sharing norms and LFOs can burden those who cannot pay by indebting them to others and adding “relational work” to their lives.